2005
DOI: 10.1128/aem.71.11.6689-6697.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Shewanella baltica as the Most Important H 2 S-Producing Species during Iced Storage of Danish Marine Fish

Abstract: Shewanella putrefaciens has been considered the main spoilage bacteria of low-temperature stored marine seafood. However, psychrotropic Shewanella have been reclassified during recent years, and the purpose of the present study was to determine whether any of the new Shewanella species are important in fish spoilage. More than 500 H 2 S-producing strains were isolated from iced stored marine fish (cod, plaice, and flounder) caught in the Baltic Sea during winter or summer time. All strains were identified as S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(120 citation statements)
references
References 45 publications
3
115
2
Order By: Relevance
“…Shewanalla spp. were recovered in this study, but this is not surprising as [47] demonstrated the presence of cells on newly caught fish. It should not be overlooked that the organisms may be opportunistic human pathogens, being associated with bacteraemia and skin and soft tissue infections [48; 49].…”
Section: Discussionmentioning
confidence: 83%
“…Shewanalla spp. were recovered in this study, but this is not surprising as [47] demonstrated the presence of cells on newly caught fish. It should not be overlooked that the organisms may be opportunistic human pathogens, being associated with bacteraemia and skin and soft tissue infections [48; 49].…”
Section: Discussionmentioning
confidence: 83%
“…Bath, the unique type I methanotroph in the databank, and in a number of marine bacteria. Among the marine bacteria belonging to the genus Shewanella , cls homologues were absent present in mesophylic species and absent in most of psychrotrophic species including Shewanella baltica and Shewanella putrefaciens (Fonnesbech Vogel et al 2005). This fact is noteworthy, because there is molecular evidence that C. fusca belongs to the psychrophilic group of type I methanotrophs (Vigliotta et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All of the thawing treatments gave non-detectable values for H 2 S-producing bacteria. Some of these bacteria are capable of reducing trimethylamine N-oxide (TMAO) and also degrading sulphur-containing amino acids and producing volatile sulphides including H 2 S (18,33,53). A number of these bacteria, namely Shewanella putrefaciens, pose health risk and have been shown to be inversely related to the remaining shelf-life of seafood products (18).…”
Section: Physical and Chemical Analysismentioning
confidence: 99%